Did You Say My Patient Was Radioactive? A Case Report - Horan, Patrick (International Journal of Paramedicine, 2025)
A local Advanced Life Support (ALS) ambulance was dispatched for a medical patient experiencing a respiratory emergency. Part of the additional information presented from the Public Safety Answer Point (PSAP) reported that the patient had received radioactive therapy, and they were warned not to come into contact with other people due to radiological concerns. The crew on the ALS unit immediately realized that while they were trained in accordance with OSHA 29 CFR 1910.120 at the technician level, they had neither the equipment nor specialized experience in radiation to know best practices for this situation. They requested the Hazardous Materials Duty Officer to assist with medical guidance and radiological understanding. Thankfully the on duty Hazardous Materials Duty Officer (HMDO) was also a paramedic and the designated radiological officer was able to offer clinical guidance, but this incident demonstrated the deficiencies that exist in the paramedic knowledge set and the need for specialized training options. The patient believed they were having an allergic reaction resulting in respiratory distress while the crew were traversing an unknown territory of brachytherapy and how that may be impacting the patient. While the patient was able to be managed relatively easily based on their symptoms with minimally invasive therapies, this highlighted the need for specialized resources and access to experts.